Pseudoxanthoma Elasticum Papillary Dermal Elastolysis: A Case Report - Rubina Alves; Lurdes Ferreira; Esmeralda Vale; Olívia Bordalo (Dermatology Research and Practice)
PXE-PDE is a rare clinicopathological entity with few cases reported. It affects more often elderly women and is characterized by asymptomatic bilateral and symmetrical yellowish papules localized predominantly on the neck and supraclavicular regions. It is clinically similar to Pseudoxanthoma Elasticum. The authors report a case of a 64-year-old woman presenting asymptomatic, yellowish, non-follicular papules, affecting the occipital and the posterior region of the neck for 1 year. The patient denied pruritic or inflammatory changes, marked solar exposition or trauma on the affected areas. Routine laboratory studies: thoracic x-ray and ophthalmologic examination were normal. The histopathologic examination of a biopsy of one of the cutaneous lesions showed an absence of elastic fibers in the papillary dermis.The diagnosis of Pseudoxanthoma Elasticum—like Papillary Dermal Elastolysis (PXE-PDE) was made. Of great importance is the differential diagnosis with Pseudoxanthoma elasticum (PXE), but we have also to consider other elastolytic disorders: mid-dermal elastolysis (MDE), linear focal elastosis (LFE) and white fibrous papulosis of the neck (WFPN). Until know, there is no effective treatment for this pathology.